Analysis of the Effects of Financial Ratios on the Dividend Policies of Lq-45 Companies in the 2019-2023 Period - Wardani, Ni Putu Nila Puspita; Muttaqin, Aminnullah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to analyze the influence of financial ratios on dividend policy in companies included in the LQ-45 index from 2019 to 2023. This research uses a quantitative method with data panel regression analysis. Based on purposive sampling technique, 17 companies were studied using secondary data from the LQ-45 Fact Sheet on the Indonesia Stock Exchange. This study found that leverage, profitability, and liquidity ratios significantly influence dividend policy. The results show that the Debt to Asset Ratio (DAR) Return on Assets (ROA), and Current Ratio have a significant and negative impact on the Dividend Payout Ratio (DPR), while the Price to Book Value has a significant positive impact on DPR. On the other hand, the Earning per Share (EPS) does not have a significant effect on dividend policy.